STRATEGI REBRANDING MEKARI DALAM MENINGKATKAN BRAND EQUITY - Harahap, Halomoan; Rinaldi, Adinda Aurel (Lembaga Penerbitan Universitas Esa Unggul, 2024)
This research aims to determine Mekari's rebranding strategy in increasing brand equity. This activity was carried out through in-depth interviews, observation and documentation. This research uses descriptive qualitative research with a case study method. The results of the research that has been carried out can show that Mekari has several strategies to increase brand equity after rebranding. The strategy used by Mekari to increase brand equity is by creating a technology event called the Mekari Conference. Apart from that, Mekari also utilizes the digital world, such as social media and media releases. All strategies carried out by Mekari are the result of intervention from employees, both CEO, C level, and especially employees who deal directly with customers such as the marketing, sales, customer support & success teams. Keyword: strategy, rebranding, brand equity.